2008
DOI: 10.1002/anie.200703953
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Flocculating/Self‐Dispersing Oscillation of Microgels

Abstract: Self‐oscillating microgels have been obtained by introducing a Ru catalyst for the Belousov–Zhabotinsky (BZ) reaction into a cross‐linked copolymer. In this microgel system, the chemical energy of the BZ reaction is converted to rhythmic swelling/deswelling with self‐flocculating/self‐dispersing oscillation of the microgel around its phase‐transition temperature (see scheme; Ru(bpy)3 denotes a Ru tris‐bipyridine complex bearing a vinyl group).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
136
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 121 publications
(137 citation statements)
references
References 43 publications
1
136
0
Order By: Relevance
“…This was mainly due to the difference in microgel concentrations (0.0001 wt % for the DLS study and 0.2 wt % for the oscillation study); we have previously confirmed that microgel concentration significantly affects the state of microgel flocculation. 19 Based on the above-mentioned results for DLS and SAXS, we were able to understand the changes in internal microscopic structures of the NRu microgels during the swelling/deswelling or dispersing/flocculating oscillations. Here, we focused on the relationship between hydrodynamic diameter (D h ) ( Figure 2b) and ξ (Figure 6) of the NRu microgels as a function of temperature.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was mainly due to the difference in microgel concentrations (0.0001 wt % for the DLS study and 0.2 wt % for the oscillation study); we have previously confirmed that microgel concentration significantly affects the state of microgel flocculation. 19 Based on the above-mentioned results for DLS and SAXS, we were able to understand the changes in internal microscopic structures of the NRu microgels during the swelling/deswelling or dispersing/flocculating oscillations. Here, we focused on the relationship between hydrodynamic diameter (D h ) ( Figure 2b) and ξ (Figure 6) of the NRu microgels as a function of temperature.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In addition, due to colloidal instability when thermoresponsive microgels are deswollen under high ionic strength (here, the BZ reaction proceeds only under high ionic strength, typically greater than 0.3 M 21 ), the microgels showed dispersing/flocculating oscillation within a narrow temperature range near critical flocculation temperature. 19,20 From this, we demonstrated that the microgels could be used as constituents of self-beating micropumps. 25 Other than their use as micro-oscillators, more recently it has been reported that Ru(bpy) 3 complex copolymerized pNIPAm microgels can also be used for enhancement of electrogenerated chemiluminescence 28 or may lead to the realization of artificial photosynthetic systems.…”
Section: ■ Introductionmentioning
confidence: 95%
“…In addition to analyzing the polymer solutions, we prepared submicron-sized poly(NIPAAm-co-Ru(bpy) 3 ) gel beads by surfactant-free aqueous precipitation polymerization, and analyzed the oscillating behavior of the microgel dispersions [20][21][22][23][24]. At low temperatures (20-26.5 • C), on raising the temperature, the amplitude of the oscillation became larger.…”
Section: Self-oscillating Polymer Solution and Microgel Dispersion Asmentioning
confidence: 99%
“…We then prepared submicron-sized poly(NIPAAm-co-Ru(bpy) 2+ 3 ) gel beads by surfactant-free aqueous precipitation polymerization, and analyzed their oscillating behaviors [34][35][36][37]. for the microgel dispersions.…”
Section: Self-flocculating/dispersing Oscillation Of Microgelsmentioning
confidence: 99%